Susceptibility and barriers to infection of Colorado mosquitoes with Rift Valley fever virus. - Daniel A Hartman; Nicholas A Bergren; Therese Kondash; William Schlatmann; Colleen T Webb; Rebekah C Kading (Public Library of Science (PLoS), 2021)
Rift Valley fever virus (RVFV) causes morbidity and mortality in humans and domestic ungulates in sub-Saharan Africa, Egypt, and the Arabian Peninsula. Mosquito vectors transmit RVFV between vertebrates by bite, and also vertically to produce infectious progeny. Arrival of RVFV into the United States by infected mosquitoes or humans could result in significant impacts on food security, human health, and wildlife health. Elucidation of the vectors involved in the post-introduction RVFV ecology is paramount to rapid implementation of vector control. We performed vector competence experiments in which field-collected mosquitoes were orally exposed to an epidemic strain of RVFV via infectious blood meals. We targeted floodwater Aedes species known to feed on cattle, and/or deer species (Aedes melanimon Dyar, Aedes increpitus Dyar, Aedes vexans [Meigen]). Two permanent-water-breeding species were targeted as well: Culiseta inornata (Williston) of unknown competence considering United States populations, and Culex tarsalis Coquillett as a control species for which transmission efficiency is known. We tested the potential for midgut infection, midgut escape (dissemination), ovarian infection (vertical transmission), and transmission by bite (infectious saliva). Tissues were assayed by plaque assay and RT-qPCR, to quantify infectious virus and confirm virus identity. Tissue infection data were analyzed using a within-host model under a Bayesian framework to determine the probabilities of infection outcomes (midgut-limited infection, disseminated infection, etc.) while estimating barriers to infection between tissues. Permanent-water-breeding mosquitoes (Cx. tarsalis and Cs. inornata) exhibited more efficient horizontal transmission, as well as potential for vertical transmission, which is contrary to the current assumptions of RVFV ecology. Barrier estimates trended higher for Aedes spp., suggesting systemic factors in the differences between these species and Cx. tarsalis and Cs. inornata. These data indicate higher potential for vertical transmission than previously appreciated, and support the consensus of RVFV transmission including a broad range of potential vectors.